CHARACTERIZATION OF KARANGNUNGGAL KAOLIN AS RAW MATERIALS FOR CERAMIC - Widodo Widodo; Subari Subari; Bagus D. Erlangga (Puslitbang tekMIRA, 2016)
Kaolin from Karangnunggal had been characterized. This kaolin has a brownish white in color and is associated with tuff. To identify characteristics, the samples was analyzed by XRD, optical microscope, AAS, and SEM. The results showed that the kaolin consisted of kaolinite, halloysite, cristobalite, dickite, muscovite, illit and hematit while petrographic analysis describes halloysite, kaolinite, dickite, and quartz. SEM analysis showed the crystal forms such as kaolinite, halloysite and dickite; while chemical analysis confirmed that kaolin composition comprised SiO2 = 65.78 %, Al2O3 = 19.55 %, Fe2O3 = 0.90 % and LOI = 8.29 %. Based on characterization results Karangnunggal kaolin originated from tuff alteration. Referring to such properties, this kaolin can be used as raw material for white ceramic products such as sanitary, ceramic tiles and insulation.